A C. elegans genome-wide RNAi screen for altered levamisole sensitivity identifies genes required for muscle function. Issue 4 (13th March 2021) - Chaya, Timothy; Patel, Shrey; Smith, Erin M; Lam, Andy; Miller, Elaine N; Clupper, Michael; Kervin, Kirsten; Tanis, Jessica E
Abstract: At the neuromuscular junction (NMJ), postsynaptic ionotropic acetylcholine receptors (AChRs) transduce a chemical signal released from a cholinergic motor neuron into an electrical signal to induce muscle contraction. To identify regulators of postsynaptic function, we conducted a genome-wide RNAi screen for genes required for proper response to levamisole, a pharmacological agonist of ionotropic L-AChRs at the Caenorhabditis elegans NMJ. A total of 117 gene knockdowns were found to cause levamisole hypersensitivity, while 18 resulted in levamisole resistance. Our screen identified conserved genes important for muscle function including some that are mutated in congenital myasthenic syndrome, congenital muscular dystrophy, congenital myopathy, myotonic dystrophy, and mitochondrial myopathy. Of the genes found in the screen, we further investigated those predicted to play a role in endocytosis of cell surface receptors. Loss of the Epsin homolog epn-1 caused levamisole hypersensitivity and had opposing effects on the levels of postsynaptic L-AChRs and GABAA receptors, resulting in increased and decreased abundance, respectively. We also examined other genes that resulted in a levamisole-hypersensitive phenotype when knocked down including gas-1, which functions in Complex I of the mitochondrial electron transport chain. Consistent with altered ATP synthesis impacting levamisole response, treatment of wild-type animals with levamisole resulted in L-AChR–dependent depletion of ATP levels. These results suggest that the paralytic effects of levamisole ultimately lead to metabolic exhaustion.